Synthesis and screening of small-molecule α-helix mimetic libraries targeting protein–protein interactions. (February 2015) - Moon, Heejo; Lim, Hyun-Suk
Highlights: We highlight recent development of small-molecule α-helix mimetics. We review solid-phase synthesis of small-molecule α-helix mimetics. We highlight HTS methods for the identification of small-molecule α-helix mimetics. Abstract : α-Helices are the most common protein secondary structure and play a key role in mediating many protein–protein interactions (PPIs) by serving as recognition motifs. Given that aberrant α-helix-mediated PPIs are linked to various disease states, targeting such interactions with small-molecules represents an attractive strategy to develop therapeutic candidates for the related diseases. Over the last decade, significant efforts have been directed toward developing α-helix mimetic small-molecules that can modulate α-helix-mediated PPIs. In this review, we will highlight recent advances in the development of non-peptidic, small-molecule α-helix mimetics with a focus on library synthesis and screening methods to efficiently discover small-molecule α-helix mimetics.